2018
DOI: 10.1111/itor.12564
|View full text |Cite
|
Sign up to set email alerts
|

Cold chain investment and pricing decisions in a fresh food supply chain

Abstract: Cold chains play an important role in reducing food spoilage, attracting food safety sensitive consumers, and guaranteeing food safety. Despite these advantages, the implementation of cold chains also calls for massive investment. Considering both costs and benefits of cold chains, our research established an optimization model for a fresh food supply chain to maximize its members' profits. Optimal investment levels of cold chain construction and advertisement, along with optimal pricing, were determined. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
(47 reference statements)
1
27
0
Order By: Relevance
“…Wang and Zhao determined the optimal investment levels of the cold chain construction, advertisement, and optimal pricing in a fresh food supply chain. ey found that collaborative cold chain investment and collaborative pricing are superior strategies for the supply chain [14].…”
Section: Relevant Literaturementioning
confidence: 99%
“…Wang and Zhao determined the optimal investment levels of the cold chain construction, advertisement, and optimal pricing in a fresh food supply chain. ey found that collaborative cold chain investment and collaborative pricing are superior strategies for the supply chain [14].…”
Section: Relevant Literaturementioning
confidence: 99%
“…The cold chain logistics is crucial to protecting food from spoilage during transportation and storage. 7 In China, the government and many logistics enterprises have invested a lot of capital to build a cold chain logistics network. 8 The evaluation and selection of logistics distribution centers is of great significance in constructing green cold chain logistics networks.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of living standard makes people have high requirements for the quality of fruits and meat. The cold chain logistics is crucial to protecting food from spoilage during transportation and storage 7 . In China, the government and many logistics enterprises have invested a lot of capital to build a cold chain logistics network 8 .…”
Section: Introductionmentioning
confidence: 99%
“…() worked on deciding lead time, ordering cost, and cyclic replenishment mechanism to optimize total costs. Wang and Zhao () reviewed a fresh food supply chain and they optimized their model to maximize the partners’ profits. Additionally, optimum pricing, investment levels, and also advertisement of cold chain were determined.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%